RETRACTED ARTICLE: Ras-ERK signalling represses H1.4 phosphorylation at serine 36 to promote non-small-cell lung carcinoma cells growth and migration. Issue 1 (4th December 2019) - Shi, Shaomin; Zhang, Jingzhe; Liu, Meihan; Dong, Hang; Li, Ning
Abstract : We, the Editors and Publisher of the journal  Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Shaomin Shi, Jingzhe Zhang, Meihan Liu, Hang Dong & Ning Li (2019) Ras-ERK signalling represses H1.4 phosphorylation at serine 36 to promote non-small-cell lung carcinoma cells growth and migration. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 2343–2351, DOI: 10.1080/21691401.2019.1624558 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.